Asia and Europe : essays and speeches - Koh, Tommy T. B. (Tommy Thong Bee), 1937- (World Scientific Pub. : Asia-Europe Foundation, 2000)
"This collection of essays and speeches by Professor Tommy Koh were delivered and written in his capacity as the Executive Director of ASEF. It contains his thoughts on the three pillars of Asia-Europe relations: politics, economics, and civil society. Readers will find in this book his assessment of some of the key trends shaping the emerging world order and some crucial events affecting the transformation of Asia and Europe. He points to synergies between the two continents but does not hesitate to note differences in outlook which have to be recognised and respected. This book is an interesting contribution to the growing literature on a new partnership in the making."--Jacket